Bahasa dan kognisi Studi korelasional tentang pemahaman teks ekspositori dan berpikir deduktif dan induktif pada siswa SMA - Ramelan, Ratih (Wacana, Journal of the Humanities of Indonesia, 2008)
This correlational study is to show the role of deductive and inductive reasoning abilities as aspects of cognitive development on expository text comprehension among high school students who already have a capacity to think in conceptual and hyphotetical ways and to examine how they correlate and influence the text comprehension process. This study has broaden our knowledge of language and thinking, as it is different from other previous studies that focused on comprehension process among elementary students, narrative, reading strategies, and comprehension difficulties. It is found that deductive reasoning is more significantly correlated to expository text comprehension than inductive reasoning. There is other significant differences between natural sciences and social sciences students in expository text comprehension and deductive reasoning, where the average scores of the natural sciences students on both variables are higher than those of social sciences students. It shows that the ability to analisesyntesise, to relate some basic elements of a text, and to draw a conclusion or main idea of the text support the process of expository text comprehension, and can be taught and developed by learning process. Meanwhile, inductive reasoning ability is significantly different between male and female students, and it does not correlate to expository text comprehension.